A systematic study of Old World Phyllomya Robineau-Desvoidy (Diptera: Tachinidae) - Shima, Hiroshi (Zootaxa, 2022)
Twenty-one species of the genus Phyllomya Robineau-Desvoidy, 1830 are recognized from the Old World, three of which are described as new to science: P. arctogena Shima & Tachi, sp. nov., P. chaoi Shima & Zhang, sp. nov., and P. sichuana Shima & Zhang, sp. nov. Phyllomya pubiseta (Mesnil, 1953) comb. nov. is proposed for Hypostena pubiseta Mesnil, 1953. The male and female terminalia of most species are described and illustrated and the first instar larvae of 15 species are described and photographed for the first time. A key to the 21 known species of Old World Phyllomya is provided.